ON MOD(3)-EDGE-MAGIC GRAPHS - Lee, Sin-Min; Schaffer, Karl; Su, Hsin-Hao; Wang, Yung-Chin (Journal of the Indonesian Mathematical Society, 2011)
Let G be a (p, q)-graph in which the edges are labeled 1, 2, . . . , q. The vertex sum for a vertex v is the sum of the labels of the incident edges at v. If the vertex sums are constant, modulo k, where k= 2, then G is said to be Mod(k)-edge-magic. When k = p, Mod(p)-edge-magic graph is the edge-magic graph which was introduced by the Lee, Seah and Tan in [9]. In this paper we investigate graphs which are Mod(3)-edge-magic.DOI :Â http://dx.doi.org/10.22342/jims.0.0.81.